2001
DOI: 10.1128/jb.183.20.5870-5876.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osmC Gene Expression by the Two-Component System rcsB-rcsC in Escherichia coli

Abstract: The Escherichia coli osmC gene encodes an envelope protein of unknown function whose expression depends on osmotic pressure and growth phase. The gene is transcribed from two overlapping promoters, osmCp 1 and osmCp 2 . Several factors regulating these promoters have been reported. The leucine-responsive protein Lrp represses osmCp 1 and activates osmCp 2 , the nucleoid-associated protein H-NS represses both promoters, and the stationary-phase sigma factor s specifically recognizes osmCp 2 . This work reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 38 publications
2
98
0
Order By: Relevance
“…Like OmpRϳP, RcsBϳP represses flagellar synthesis directly (138,330). In addition, RcsBϳP activates both colanic acid biosynthesis (433) and at least one acetylϳP-responsive stress effector (osmC) (112). Several other acetylϳP-responsive genes are regulated by RcsC, the cognate HK of RcsB, suggesting that they might also be regulated by RcsB.…”
Section: Evidence In Vitromentioning
confidence: 99%
“…Like OmpRϳP, RcsBϳP represses flagellar synthesis directly (138,330). In addition, RcsBϳP activates both colanic acid biosynthesis (433) and at least one acetylϳP-responsive stress effector (osmC) (112). Several other acetylϳP-responsive genes are regulated by RcsC, the cognate HK of RcsB, suggesting that they might also be regulated by RcsB.…”
Section: Evidence In Vitromentioning
confidence: 99%
“…In addition to the cps genes and several other genes whose regulation by the Rcs system has been fairly thoroughly investigated (5,10,13,15,18,34), many genes were recently identified as putative Rcs regulon members (17,22,43). Some are positively and others are negatively regulated.…”
Section: Vol 186 2004mentioning
confidence: 99%
“…The rcsF gene product was reported to activate RcsB when overproduced (19), but its function in signal transduction was not clear until recently, when Hagiwara et al (22) showed its involvement in Rcs signaling in response to glucose and zinc at 20°C. The Rcs system was shown to affect the expression of tolQRA (10), rcsA (15), ftsAZ (5), osmC (13), rprA (34), and flhDC (18). Recent transcriptome analyses using DNA arrays identified many other genes that are under direct or indirect control of the Rcs system (17,22,43).…”
mentioning
confidence: 99%
“…The Rcs phosphorelay has been implicated in the synthesis of virulence factors in Pcc and other plant-pathogenic bacteria and also in human pathogens (Hinchliffe et al, 2008;Mouslim et al, 2004;Wang et al, 2009Wang et al, , 2007. RcsB activates the biosynthesis of capsular exopolysaccharides, transcription of the cell division gene, ftsZ, transcription of a cell envelope protein, osmC, and transcription of RprA RNA to increase expression of the stationary-phase sigma factor, RpoS, in E. coli (Carballes et al, 1999;Davalos-Garcia et al, 2001;Gervais et al, 1992;Gottesman et al, 1985;Majdalani et al, 2002). Francez-Charlot et al (2003) demonstrated that the Rcs phosphorelay system represses motility through the direct binding of RcsB to the promoter of flhDC in E. coli.…”
Section: Introductionmentioning
confidence: 99%